Usage control architecture options for data sovereignty in business ecosystems. Issue 3 (4th June 2019) - Zrenner, Johannes; Möller, Frederik Oliver; Jung, Christian; Eitel, Andreas; Otto, Boris
Abstract : Purpose: Current business challenges force companies to exchange critical and sensitive data. The data provider pays great attention to the usage of their data and wants to control it by policies. The purpose of this paper is to develop usage control architecture options to enable data sovereignty in business ecosystems. Design/methodology/approach: The architecture options are developed following the design science research process. Based on requirements from an automotive use case, the authors develop architecture options. The different architecture options are demonstrated and evaluated based on the case study with practitioners from the automotive industry. Findings: This paper introduces different architecture options for implementing usage control (UC). The proposed architecture options represent solutions for UC in business ecosystems. The comparison of the architecture options shows the respective advantages and disadvantages for data provider and data consumer. Research limitations/implications: In this work, the authors address only one case stemming from the German automotive sector. Practical implications: Technical enforcement of data providers policies instead of relying on trust to support collaborative data exchange between companies. Originality/value: This research is among the first to introduce architecture options that provide a technical concept for the implementation of data sovereignty in business ecosystems using UC. Consequently, it supports the decision process for the technical implementation of data sovereignty.